Controlled drug release and electroconductive performance of 3D printed scaffolds for neural tissue regeneration - Oktay, Busra; Ciftci, Fatih; Abdulazez, Israa F.; Bingol, Ayse Betul; Kose, Alpay; Erarslan, Azime; Ustundag, Cem Bulent (SPRINGER, 2026)
Nerve cell repair is a complex process influenced by genetic factors, damage severity, and treatment type. Although nerve tissue engineering has advanced, many scaffolds still fail to mimic the natural electrical properties of nerve tissue or deliver drugs effectively. To address these issues, this study presents a multifunctional scaffold designed to support nerve regeneration while reducing inflammation and pain. The scaffold was fabricated using 3D microextrusion printing, allowing precise control over geometry and composition. Polyvinyl alcohol (PVA) and collagen (Col) provided biocompatibility and biodegradability, while reduced graphene oxide (rGO) enhanced electrical conductivity. Amoxicillin (Amox) and ibuprofen (Ibu) were incorporated for antibacterial and anti-inflammatory effects. The scaffold exhibited a conductivity of (5.83 +/- 0.65) x 10(-3) S/m, and sustained drug release, with amoxicillin reaching similar to 0.6 mg/L and ibuprofen similar to 0.12 mg/L after 480 min. It showed strong antibacterial activity, with inhibition zones of 28.3 +/- 3.32 mm (E. coli) and 18.34 +/- 2.83 mm (S. aureus). Mechanically, it withstood similar to 5.5 MPa of stress and over 150% tensile strain. Cell viability exceeded 120%, indicating excellent biocompatibility. These results suggest the scaffold effectively integrates conductivity, structural strength, and therapeutic delivery to promote nerve regeneration.
Keywords: GRAPHENE OXIDE; NANOCOMPOSITE; FABRICATION; NANOFIBERS; HYDROGELS; FIBERS; CELLS; Engineering; Materials Science